Anti-bacterial self-assembled nanotubes of cyclic d, l-alpha-peptides - Al-Sayah, Mohammad (2007)
Cyclic D, L‐α‐peptides can be designed to spontaneously partition into lipid and cell membranes where they self‐assemble into membrane‐permeating nanotubes and result in disruption of membrane potentials leading to rapid cell death. The self‐assembly of the flat ring‐shaped cyclic D, L‐α‐peptides in lipid membranes is based on the formation of intermolecular hydrogen‐bonds through the perpendicular backbone amide groups. Single channel conductance measurements and proton‐transfer assays have demonstrated the ability of such constructs to act as trans‐membrane channels while dye‐release assays have been employed to determine the pore size created by the self‐assembled structures. The dynamics of the self‐assembly of pyrene‐labeled cyclic peptides into nanotubes in lipid membranes were monitored through the change in the fluorescence of pyrenes and the bio‐activity is studied through MIC assays.